2023
DOI: 10.3390/ijms24043709
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Iron and LRRK2 in a 6-OHDA-Induced Parkinson’s Disease Model

Abstract: The pathogenesis of Parkinson’s disease (PD) is very complex and still needs further exploration. Leucine-rich repeat kinase 2 (LRRK2) is associated with familial PD in mutant forms and sporadic PD in the wild-type form. Abnormal iron accumulation is found in the substantia nigra of PD patients, but its exact effects are not very clear. Here, we show that iron dextran exacerbates the neurological deficit and loss of dopaminergic neurons in 6-OHDA lesioned rats. 6-OHDA and ferric ammonium citrate (FAC) signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…FAC can catalyze the phosphorylation of S935 and S1292 of LRRK2, significantly increasing its activity. Active LRRK2 accelerates ferrous iron uptake, indicating a relationship between iron and LRRK2 in dopaminergic neurons [ 151 ].…”
Section: Role Of Iron In Neurological Diseasesmentioning
confidence: 99%
“…FAC can catalyze the phosphorylation of S935 and S1292 of LRRK2, significantly increasing its activity. Active LRRK2 accelerates ferrous iron uptake, indicating a relationship between iron and LRRK2 in dopaminergic neurons [ 151 ].…”
Section: Role Of Iron In Neurological Diseasesmentioning
confidence: 99%
“…Through the assessment of PD patients, it has been observed that the iron content in glial and dopaminergic neurons is abnormally elevated compared to that in healthy individuals, and this elevation is positively associated with the severity of PD [ 108 , 109 , 110 ]. Research has identified the formation of Lewy bodies, composed mainly of α-synuclein nucleoprotein [ 111 , 112 ], as a distinctive hallmark of PD, occurring within the cytoplasm of substantia nigra neurons [ 113 , 114 ].…”
Section: Acsl4 In Neurological Diseases and Injuriesmentioning
confidence: 99%
“…Traditionally, it has been difficult to treat a disease without proper knowledge of the underlying etiologies. In view of this, Sheu et al [12] and Jia et al [13] reported novel underlying molecular changes occurring in different situations within NDs. Although the BBB has been associated in protecting the brain from peripheral insults, BBB disruption occurs during various stages of different NDs [19], and this may allow molecules like thrombin to invade brain tissue.…”
mentioning
confidence: 99%
“…Some of the major obstacles in the field of ND therapy and disease management include limited therapeutic options, especially due to ineffective drug delivery methods; unknown etiological factors; and complications from other concurrent pathological conditions [8][9][10]. The research work presented in this Special Issue encompasses various aspects of these obstacles in ND research and presents novel aspects of drug delivery [11], molecular mechanisms associated with ND etiologies [12,13], the molecular pathways shared between diseases [14,15], and therapeutic approaches [16,17].…”
mentioning
confidence: 99%